Finance and accounting for nonfinancial managers - Weaver, Samuel C.; Weston, J. Fred (New York : McGraw-Hill, 2001)
"Finance and Accounting for Nonfinancial Managers helps nonfinancial managers make financial decisions with confidence. This hands-on book details the strategies, elements, and instruction found in today's finest business schools and executive education seminars, then outlines a step-by-step model for understanding and acting on the numbers that come across your desk.
CEOs, CIOs, COOs, and nonfinancial managers can use its proven formulas for success, case studies, exercises, charts, checklists, and quizzes."--BOOK JACKET.
Includes index.
Keywords: Finance; Accounting